Undersampled single-shell to MSMT fODF reconstruction using CNN-based ODE solver. (March 2023) - Jha, Ranjeet Ranjan; Kumar, B.V. Rathish; Pathak, Sudhir K.; Schneider, Walter; Bhavsar, Arnav; Nigam, Aditya
Highlights: Reconstruction of MSMT fODF from only full or undersampled Single-shell dMRI ( b = 1000 s / m m 2 ) in spherical harmonics space. Additionally, taking only a few gradient directions, i.e., six as input, we can predict MSMT fODF accurately with 45 coefficients. Proposed architecture consists of deep learning-based three-step Adam-Bash-forth modules with third-order Runge-Kutta triggerer. In addition, several losses have been considered like L1, and Total Variation Loss for optimizing the training. Validation has been done on publicly available dataset, qualitatively as well as quantitatively. Abstract: Background and Objective: Diffusion MRI (dMRI) has been considered one of the most popular non-invasive techniques for studying the human brain's white matter (WM). dMRI is used to delineate the brain's microstructure by approximating the WM region's fiber tracts. The achieved fiber tracts can be utilized to assess mental diseases like Multiple sclerosis, ADHD, Seizures, Intellectual disability, and others. New techniques such as high angular resolution diffusion-weighted imaging (HARDI) have been developed, providing precise fiber directions, and overcoming the limitation of traditional DTI. Unlike Single-shell, Multi-shell HARDI provides tissue fractions for white matter, gray matter, and cerebrospinal fluid, resulting in a Multi-shell Multi-tissue fiber orientation distribution function (MSMT fODF). This MSMT fODF comes up with more precise fiber directions than a Single-shell, which helps to get correct fiber tracts. In addition, various multi-compartment diffusion models, including as CHARMED and NODDI, have been developed to describe the brain tissue microstructural information. This type of model requires multi-shell data to obtain more specific tissue microstructural information. However, a major concern with multi-shell is that it takes a longer scanning time restricting its use in clinical applications. In addition, most of the existing dMRI scanners with low gradient strengths commonly acquire a single b-value (shell) upto b = 1000 s / m m 2 due to SNR (Signal-to-noise ratio) reasons and severe imaging artifacts. Methods: To address this issue, we propose a CNN-based ordinary differential equations solver for the reconstruction of MSMT fODF from under-sampled and fully sampled Single-shell ( b = 1000 s / m m 2 ) dMRI. The proposed architecture consists of CNN-based Adams-Bash-forth and Runge-Kutta modules along with two loss functions, including L 1 and total variation. Results: We have shown quantitative results and visualization of fODF, fiber tracts, and structural connectivity for several brain regions on the publicly available HCP dataset. In addition, the obtained angular correlation coefficients for white matter and full brain are high, showing the proposed network's utility.Finally, we have also demonstrated the effect of noise by adjusting SNR from 5 to 50 and observed the network robustness. Conclusion: We can conclude that our model can accurately predict MSMT fODF from under-sampled or fully sampled Single-shell dMRI volumes.